Do disease specific characteristics add to the explanation of mobility limitations in patients with different chronic diseases? A study in The Netherlands. Issue 6 (December 1997) - Kriegsman, D M; Deeg, D J; van Eijk, J T; Penninx, B W; Boeke, A J
Abstract : STUDY OBJECTIVES: To determine whether disease specific characteristics, reflecting clinical disease severity, add to the explanation of mobility limitations in patients with specific chronic diseases. DESIGN AND SETTING: Cross sectional study of survey data from community dwelling elderly people, aged 55-85 years, in the Netherlands. PARTICIPANTS AND METHODS: The additional explanation of mobility limitations by disease specific characteristics was examined by logistic regression analyses on data from 2830 community dwelling elderly people. MAIN RESULTS: In the total sample, chronic non-specific lung disease, cardiac disease, peripheral atherosclerosis, diabetes mellitus, stroke, arthritis and cancer (the index diseases), were all independently associated with mobility limitations. Adjusted for age, sex, comorbidity, and medical treatment disease specific characteristics that explain the association between disease and mobility mostly reflect decreased endurance capacity (shortness of breath and disturbed night rest in chronic non-specific lung disease, angina pectoris and congestive heart failure in cardiac disease), or are directly related to mobility function (stiffness and lower body complaints in arthritis). For atherosclerosis and diabetes mellitus, disease specific characteristics did not add to the explanation of mobility limitations. CONCLUSIONS: The results provide evidence that, to obtain more detailed information about the differential impact of chronic diseases on mobility, disease specific characteristics are important to take into account.